Association between aortomesenteric angle and symptomatic spontaneous isolated superior mesenteric artery dissection - Yadong Shi; Yangyi Zhou; Yuan Yuan; Liang Chen; Xu He; Haobo Su (Scientific Reports)
Abstract The purpose of this study is to investigate the association between the aortomesenteric angle (AMA) and the occurrence and image characteristics of spontaneous isolated superior mesenteric artery dissection (SISMAD). This is a single-centre retrospective case-control study. Between January 1 2013 and December 13 2022, consecutive patients with computed tomography angiography (CTA) confirmed symptomatic SISMAD were included. Controls were selected with 1:1 matches in patients with CTA of the superior mesenteric artery but without SISMAD using propensity score matching for age, sex, and body mass index. Patient demographics, symptoms, and dissection characteristics were recorded. Logistic regression was performed to assess the association between AMA and SISMAD. The study also evaluated the association between AMA and SISMAD using restricted cubic splines (RCS). The associations between AMA and the characteristics of SISMAD were evaluated. One hundred and five SISMAD patients (mean age, 54.8 ± 8.9 years) were included, and most patients were male (87.6%). Univariable analysis revealed hypertension, hyperlipemia, and AMA (all p < .001) were associated with SISMAD. An increasing AMA (adjusted OR, 1.03 per 1 ° increase in angulation) and hypertension (adjusted OR, 3.52) were identified as risk factors for SISMAD. Compared with small AMA level (< 50°), intermediate (50–71°) (adjusted OR, 2.62; 95% CI, 1.23–5.58; p = .013) and large angle level (> 71°) (adjusted OR, 4.50; 95% CI, 2.07–9.82; p < .001) were significantly associated with SISMAD. No obvious associations between AMA and the SISMAD imaging characteristics were found. Greater AMA and hypertension were independent risk factors for SISMAD.